Pollution index and load of total nitrogen and phosphate on agriculture and fisheries in Jatigede Reservoir - Zulfia Kamila Mutia; Denny Kurniadie; Dadan Sumiarsa (Jurnal Akuakultur Indonesia)
Jatigede Reservoir has an area of approximately 4,122 Ha, the purpose of Jatigede dam construction is to increase rice production with a range irrigation network system. Problems arising from the use of chemical fertilizers, regarding the development of agricultural land used to increase agricultural productivity, support food security and also activities in floating net cages (FNC) can result in a decrease in reservoir water quality, siltation of reservoirs, etc. Organic waste from FNC cultivation feed, for example nitrogen and phosphate. The purpose is to determine the pollution index of each observation station and the concentration of total nitrogen and total phosphor pollutant loads from the agriculture and fisheries sectors in Jatigede Reservoir so that it can be analyzed which activities have the most influence on pollution and determine effective countermeasures a decrease in water quality in Jatigede Reservoir. The quantitative method uses a survey method is processing data from laboratory tests using the Pollution Index and total nitrogen and phosphate pollution loads. The results of the highest pollution index are at station three of 6.08 with moderate pollution status caused by runoff from Cihonje inlet waste and FNC activities. The nitrogen parameter pollution load has a high amount of 192.13 kg/day then the amount of phosphate pollution load is 34.16 kg/day. As for good pollution control, by reducing the burden of pollution by involving the community in managing the reservoir environment, routine monitoring of reservoir water quality and mapping potential pollutant sources at each location so that problems will be quickly resolved.